Learned helplessness and its associations with illness perception, depression and anxiety among patients with systemic lupus erythematosus - Nowicka-Sauer, Katarzyna; Hajduk, Adam; Kujawska-Danecka, Hanna; Banaszkiewicz, Dorota; Czuszyńska, Zenobia; Smoleńska, Żaneta; Siebert, Janusz (Family Medicine & Primary Care Review, 2017)
Background. Systemic lupus erythematosus (SLE ) is a chronic, multi-organ disease that significantly impacts patients’ psychological functioning. Learned helplessness (LH) and illness perception have been proven to influence patients’ emotional and physical state and treatment adherence. Objectives . The study is aimed at exploring learned helplessness and its relationship with illness perception, depression and anxiety among patients with SLE . Material and methods. The participants were 59 outpatients diagnosed with SLE (55 women, mean age: 45.0 ± 11.7 years; mean SLE duration 11.1 years). The Rheumatology Helplessness Index (RHI), Brief Illness Perception Questionnaire (B-IPQ), Hospital Anxiety and Depression Scale (HAD S) were used. A structured interview and a review of medical files were used to gather clinical and sociodemographic data. Results . Learned helplessness was significantly positively correlated with the illness perception total score (r = 0.609), as well as illness consequences (r = 0.432), identity (r = 0.385), concern (r = 0.473) and emotional response (r = 0.543). Depression and anxiety levels were also significantly correlated with LH (r = 0.588 and r = 0.472, respectively). No significant associations were observed between LH and age, age at diagnosis, duration of the disease, disease activity, gender, education and employment status. Conclusions . 1. In patients with SLE , learned helplessness is related to experiencing more severe consequences and symptoms of SLE , as well as more intense concerns and negative emotions related to the disease. 2. Psychotherapeutic intervention aimed at patient empowerment and modification of negative cognitions seems vital in order to diminish negative psychological functioning. 3. Treatment and self-management aimed at better symptoms control and minimizing the consequences of illness may contribute to less negative cognitive and emotional illness representations.